(untitled) (Global Journal of Human-Social Science, 2024)
In this contribution we propose an attempt to understand the mystery of the failure of malagsy learners in the face of fundamental knowledge through a psychopedagogical analysis of these learning obstacles Three main psychopedagogical are therefore identified diagnose teach manage psychological and disciplinary aspects It is in vain that we propose through this article a model of psychopedagogical dynamics based on learning through culture initiated by Serge Boimare in his work We think that if teacher is capable of taking the stage of restoring the thinking machine through cultural mediation he will revitalize the knowledge of learners in difficukty by serving their interests including those of the best among them and will subsequently operate his class